HUBUNGAN EDUKASI KESEHATAN TENTANG CEDERA ANKLE DAN TERAPI LATIHANNYA TERHADAP TINGKAT PENGETAHUAN MAHASISWA KEDOKTERAN PEMAIN FUTSAL - Yohanes Jason; Zita Arieselia (Atma Jaya Catholic University of Indonesia, 2020)
Introduction: Indoor-soccer is among top ten sports that often causes injuries, with an incidence rate of 55.2 injuries per 10.000 hours of sports participation. Ankle injury is the most common and when this is not handled well, it may result in chronic ankle instability. The aim of this study was to explore the association between health education about ankle injury and exercise therapy on knowledge level among medical students who were member of indoor-soccer sport. Methods: This research was an experimental study with a cross-sectional approach, conducted at School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia with purposive sampling. Health education was provided using slideshow and the knowledge level was measured using questionnaires. Data was analyzed with a paired T-test test. Results: Total respondents were 36 students. The level of knowledge of students before being given health education about ankle injury and exercise therapy was 66.3+11.6 (mean, range 40.0 - 93.3) which was significantly increased to 78.5+6.3 (mean; range 63.3 - 96.7) after being given health education about ankle injury and exercise therapy (p value <0.05, paired T-Test test). Conclusion: There is an increased knowledge among soccer members after health education explaining about ankle injury and exercise therapy. Therefore, it is necessary to equip the players with health education before any sports begin to avoid sport injury.